If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(u + -1) = -8u + 20 Reorder the terms: -4(-1 + u) = -8u + 20 (-1 * -4 + u * -4) = -8u + 20 (4 + -4u) = -8u + 20 Reorder the terms: 4 + -4u = 20 + -8u Solving 4 + -4u = 20 + -8u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '8u' to each side of the equation. 4 + -4u + 8u = 20 + -8u + 8u Combine like terms: -4u + 8u = 4u 4 + 4u = 20 + -8u + 8u Combine like terms: -8u + 8u = 0 4 + 4u = 20 + 0 4 + 4u = 20 Add '-4' to each side of the equation. 4 + -4 + 4u = 20 + -4 Combine like terms: 4 + -4 = 0 0 + 4u = 20 + -4 4u = 20 + -4 Combine like terms: 20 + -4 = 16 4u = 16 Divide each side by '4'. u = 4 Simplifying u = 4
| A-2B+4C+6D+2E+4F=52 | | -3x+46=-2z+36 | | 2v/5-3wv=40w=10 | | A-B+C-D+E-F=-6 | | 2q+58=4q+50 | | 2s-35=131 | | 1.3h+3.7h=5 | | 50-7k=24 | | 0.8c+9=8(0.6c-2) | | 6(k+4)=3k-12 | | -2x=3x+3 | | 5z-96z+2z+4=12z-156 | | 4x+1=.15 | | 12b+3whenb=-4 | | 1/3=954/s | | 6c=3(c+4)-c | | 5z-96z+2z+4=2(6z-78) | | 1.8=0.03x-58.32 | | 4x+35x=21x+28 | | 2+4(x-7)=5-4(x-5) | | 8x+47=8(x+6) | | -1+3x=3+25x | | 5(3m-4)-8=-88 | | f(x)=x^3-28x+48 | | 6(2x+5)=2 | | x^2+3y^2-3z^2-3xy-2xz-2yz=-1997 | | -3(2g+1)+3g=6g+3 | | 6z-38=130 | | 5n^2+2n-14=-7 | | 9x-58=7x | | (8x-16)=180 | | 5n^2+2n-14n=-7 |